2019
DOI: 10.3899/jrheum.190084
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related Adverse Events Associated with Cancer Immunotherapy: A Review for the Practicing Rheumatologist

Abstract: Immune checkpoint inhibitors have revolutionized cancer therapy by blocking inhibitory pathways of the immune system to fight cancer cells. Their use is often limited by the development of autoimmune toxicities, which can affect multiple organ systems and are referred to as immune-related adverse events (irAE). Among these are rheumatologic irAE, including inflammatory arthritis, myositis, vasculitis, and others. Rheumatologic irAE seem to be different from irAE in other organs and from traditional autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 82 publications
2
28
0
Order By: Relevance
“…We described a case of polyarthritis that were reported only on five clinical trials with a range of 1% -7% in the meta-analysis of Capelli et al Dry eyes were most commonly reported with a range of incidence of 3% -24% In this study, two cases of polyarthritis and tenosynovitis after treatment of Pembrolizumabsimilar to our observation, have been also reported [7]. Time to onset of polyarthritis is generally 4 -8 weeks after initiation of ICIs, however they have been reported after one dose or up two years after receiving these therapies [3] [14]. In the majority of cases, the auto-antibodies are negative, al-…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…We described a case of polyarthritis that were reported only on five clinical trials with a range of 1% -7% in the meta-analysis of Capelli et al Dry eyes were most commonly reported with a range of incidence of 3% -24% In this study, two cases of polyarthritis and tenosynovitis after treatment of Pembrolizumabsimilar to our observation, have been also reported [7]. Time to onset of polyarthritis is generally 4 -8 weeks after initiation of ICIs, however they have been reported after one dose or up two years after receiving these therapies [3] [14]. In the majority of cases, the auto-antibodies are negative, al-…”
Section: Discussionsupporting
confidence: 73%
“…though Rheumatoid Factor (RF) or anti-citrullinated cyclic peptide positive cases have been reported[3] [15]. In our observation RF was positive with a low titer; other auto-antibodies were negative.Rh-irAES are managed according to severity assessed using Common Terminology Criteria for Adverse Events grading system[10].…”
mentioning
confidence: 43%
See 3 more Smart Citations